Excitation/Inhibition Modulators in Autism Spectrum Disorder: Current Clinical Research - Canitano, Roberto; Palumbi, Roberto (Frontiers in Neuroscience, 2021)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by social and communication abnormalities. Heterogeneity in the expression and severity of the core and associated symptoms poses difficulties in classification and the overall clinical approach. Synaptic abnormalities have been observed in preclinical ASD models. They are thought to play a major role in clinical functional abnormalities and might be modified by targeted interventions. An imbalance in excitatory to inhibitory neurotransmission (E/I imbalance), through altered glutamatergic and GABAergic neurotransmission, respectively, is thought to be implicated in the pathogenesis of ASD. Glutamatergic and GABAergic agents have been tested in clinical trials with encouraging results as to efficacy and tolerability. Further studies are needed to confirm the role of E/I modulators in the treatment of ASD and on the safety and efficacy of the current agents.